Neural networks and genome informatics - Wu, Cathy H. (Methods in computational biology and biochemistry, 2000)
A reference in the field of neural networks and genome informatics. It includes a tutorial of neural network foundations that introduces basic neural network technology and terminology. It features a discussion of special system designs for building neural networks for genome informatics, and also reviews and evaluations of methods in the field.